2017
DOI: 10.1038/cdd.2016.165
|View full text |Cite
|
Sign up to set email alerts
|

Loss of menin in osteoblast lineage affects osteocyte–osteoclast crosstalk causing osteoporosis

Abstract: During osteoporosis bone formation by osteoblasts is reduced and/or bone resorption by osteoclasts is enhanced. Currently, only a few factors have been identified in the regulation of bone integrity by osteoblast-derived osteocytes. In this study, we show that specific disruption of menin, encoded by multiple endocrine neoplasia type 1 (Men1), in osteoblasts and osteocytes caused osteoporosis despite the preservation of osteoblast differentiation and the bone formation rate. Instead, an increase in osteoclast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 32 publications
3
39
0
3
Order By: Relevance
“…We analysed gene expression patterns and intracellular signalling pathways upon C5aR1 activation and found a strong modulation of genes involved for example in the mitogen‐activated protein kinase (MAPK) and insulin pathways. Furthermore, we demonstrated that C5aR1 and TLR2 interact in osteoblasts, resulting in upregulation of the immune cell chemoattractant C‐X‐C motif chemokine 10 (CXCL10), which can induce osteoclastic bone resorption . These results suggest that complement‐activated osteoblasts are able to modulate the inflammatory milieu during inflammatory bone diseases in concert with osteoclasts and immune cells.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…We analysed gene expression patterns and intracellular signalling pathways upon C5aR1 activation and found a strong modulation of genes involved for example in the mitogen‐activated protein kinase (MAPK) and insulin pathways. Furthermore, we demonstrated that C5aR1 and TLR2 interact in osteoblasts, resulting in upregulation of the immune cell chemoattractant C‐X‐C motif chemokine 10 (CXCL10), which can induce osteoclastic bone resorption . These results suggest that complement‐activated osteoblasts are able to modulate the inflammatory milieu during inflammatory bone diseases in concert with osteoclasts and immune cells.…”
Section: Introductionmentioning
confidence: 83%
“…CXCL10 attracts mainly neutrophils, macrophages and cytotoxic T cells and is generated by many cell types, including osteoblasts, which express and secrete CXCL10 in response to bacterial challenges, namely by Salmonella and P. gingivalis . Moreover, CXCL10 was found to act osteoclastogenic, either directly or indirectly by inducing RANKL expression by T cells and osteoblasts . Furthermore, CXCL10 induction via RANKL was found to crucially contribute to bone destruction at inflamed joint areas during rheumatoid arthritis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, knockout of Men1 in the liver (using albumin promoter/ALB-Cre), a tissue not targeted in MEN1, does not lead to tumors in the liver despite the complete loss of Men1 (Scacheri, et al 2004). Other mouse models with knockout of Men1 in pancreatic endocrine cell lineages, bone cells, and intestinal cells have also helped to gain insight into the physiological actions of menin (Bonnavion, et al 2015; Kanazawa, et al 2015; Liu, et al 2017; Sundaresan, et al 2016; Veniaminova, et al 2012). These elegant studies in genetically engineered mouse models show that menin may function as a cell-type-specific tumor suppressor, and that its action is only required in MEN1-associated target tissues to prevent tumorigenesis.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%